Platform: Historiaa, ominaispiirteitä ja määritelma; The Platform – History, Characteristics, and the Definition - Timo Seppälä; Marco Halén; Jari Juhanko; Heidi Korhonen; Juri Mattila; Päivi Parviainen; Jaakko Talvitie; Heikki Ailisto; Kirsi-Maria Hyytinen; Jukka Kääriäinen; Martti Mäntylä; Sampsa Ruutu (The Research Institute of the Finnish Economy (ETLA), 2015)
– In this report we present the definition for a digital platform. We also define what kinds for characteristics and features are associated with platforms and the platform economy. This report provides background information for policy-makers on digital platforms. It also serves as an introduction to a policy implications report for the Prime Minister's Office due later in 2016. The platform economy, digital platforms and their ecosystems are rapidly changing the business models and information technology architectures across traditional industry boundaries. Internet as an operating environment has a central key role to play in this transformation. Thanks to new digital architectures, pioneering actors can now take the leap from intranet towards supply-chain and Internet centric platform train of thought. We define a platform as follows: Digital platforms refer to information technology systems upon which different actors — that is, users, service providers and other stakeholders across organizational boundaries — can carry out valued-adding activities in a multi-sided market environment governed by agreed boundary resources. Typically these actors create, offer and maintain products and services that are complementary to one another. Platforms quintessentially lure and lock in various types of actors with their network effects and economic benefits thereof. In this report we present the developmental history of platforms and the relevant terminology to their definition. We also examine the definitions of the characteristics of platforms from the standpoint of Apple's platform. Our analysis shows that there are two angles of approach to platforms: the point of view relating to the internal business operations of a company, and the wider aspect arising from managing social and technical boundary resources of Internet-based platforms ecosystems. Actors now require a new kind of grasp and strategic foresight to become significant players in the platform economy.
Keywords: L6; L8; L86; L89; 330; Platform; Platform economy; Disruption; Digitalization; Internetportal; Integriertes Informationssystem; Marktstruktur; Computerunterstützung; Informationstechnik